TAVR outcome after reclassification of aortic valve stenosis by using a hybrid continuity equation that combines computed tomography and echocardiography data. Issue 4 (19th March 2020) - Weber, Marcel; Jaenisch, Max; Spilker, Marie; Pingel, Simon; Schueler, Robert; Stundl, Anja; Sedaghat, Alexander; Hammerstingl, Christoph; Mellert, Fritz; Grube, Eberhard; Nickenig, Georg; Werner, Nikos; et al.
Abstract: Background: In the continuity equation, assumption of a round‐shaped left ventricular outflow tract (LVOT) leads to underestimation of the true aortic valve area in two‐dimensional echocardiography. The current study evaluated whether inclusion of the LVOT area, as measured by computed tomography (CT), reclassifies the degree of aortic stenosis (AS) and assessed the impact on patient outcome after transcatheter aortic valve replacement (TAVR). Methods and Results: Four hundred and twenty‐two patients with indexed aortic valve area index (AVAi) of <0.6 cm 2 /m 2, assessed by using the classical continuity equation (mean age: 81.5 ± 6.1 years, 51% female, mean left ventricular ejection fraction: 53.2 ± 13.6%), underwent TAVR and were included. After inclusion of the CT measured LVOT area into the continuity equation, the hybrid AVAi led to a reclassification of 30% ( n = 128) of patients from severe to moderate AS. Multivariate predictors for reclassification were male sex, lower mean aortic gradient, and lower annulus/LVOT ratio (all p < .01). Reclassified patients had significantly higher sST2 at baseline and higher NT‐proBNP values at baseline and 6 months follow‐up compared to non‐reclassified patients. Acute kidney injury was experienced more frequently after TAVR by reclassified patients, but no significant mortality difference occurred during 2 years of follow‐up. Conclusion: The hybrid AVAi reclassifies a significant portion of low‐gradient severe AS patients into moderate AS. Reclassified patients showed increased fibrosis and heart failure markers at baseline compared to non‐reclassified patients. But reclassification had no significant impact on mortality up to 2 years after TAVR. Routine assessment of hybrid AVAi seems not to improve further risk stratification of TAVR patients.